Do the day/night periods and tidal cycles modulate the abundance and distribution of Callinectes danae Smith, 1869 (Brachyura, Portunidae) in an estuary-bay complex from southeastern Brazil? - Pescinelli, Régis Augusto [UNESP]; Koury, Helena Ansanello [UNESP]; Bochini, Gabriel Lucas [UNESP]; Lopes, Mateus [UNESP]; Costa, Rogerio Caetano [UNESP] (Sociedade Brasileira de Carcinologia, 2020)
We investigated the abundance and spatial distribution of Callinectes danae Smith, 1869 during the day/night periods and tidal cycles in a coastal area of Brazil. Sex ratio, size class distribution, and mean sizes of males and females were also analyzed. The sampling occurred between February and March 2011 in the estuary-bay complex of São Vicente. Collections occurred in six sampling stations during both daytime and nighttime. A total of 1997 specimens were collected in the bay and 963 specimens in the estuary. The abundance of males and females differed between the bay and estuary, with males more abundant in the estuary and adult females in the bay. Crabs in all demographic categories were more abundant at night. The species distribution was intrinsically related to the interaction between environmental factors. In addition to the higher capture during nocturnal collections, a positive correlation was found between the abundance of reproductive females and salinity, while juveniles were more abundant in shallower stations and at lower salinities. Our results contribute to a better understanding of the influence of day/night periods and tidal cycles on the abundance and distribution of the swimming crab C. danae.
Keywords: Coastal waters; Crustacea; fisheries resource; population features; swimming crab